INVESTIGATING READING EXERCISE OF ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL STUDENTS - Maharani, Tri Widya; Syafira, Rizky; Amelia Putri, Hirdina Sartika Dwi Yunita (Faculty of Education and Teachers Training, 2024)
This research is aimed to analyze the reading exercise on the English textbook from X grade published by Kemendikbud. The objectives of this study are to find out the appropriateness of the 2013 curriculum implementation on the reading exercise in X grade textbook. This research used descriptive qualitative method. The focus of this research is on analysing reading exercise in every chapter from the textbook. The writers found complete fundamental competencies which are available in the materials of the book. There is a discussion about the material about song and dialogue and also, there are exercises as the tool to assess basic competence fourth. In conclusion this book has a reading exercise which is compatible with the curriculum